2016
DOI: 10.1016/j.ccell.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activity of Agonistic, Human Anti-CD40 Monoclonal Antibodies Requires Selective FcγR Engagement

Abstract: Summary While engagement of the inhibitory Fcγ-Receptor (FcγR) IIB is an absolute requirement for in vivo antitumor activity of agonistic mouse anti-CD40 monoclonal antibodies (mAbs), a similar requirement for human mAbs has been disputed. By using a mouse model humanized for its FcγRs and CD40, we revealed that FcγRIIB-engagement is essential for the activity of the human CD40 mAbs, while engagement of the activating FcγRIIA inhibits this activity. By engineering Fc variants with selective enhanced binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
197
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(201 citation statements)
references
References 38 publications
3
197
0
1
Order By: Relevance
“…Recent work has shown that engineering CP-870,893 with an IgG1 Fc domain, to enhance binding to FcγRIIB, can improve the potency of CP-870,893 as measured by its ability to invoke antigen-specific T cell immunity in a novel humanized mouse model [31]. FcγRIIB is the only inhibitory Fc receptor and variations in the gene encoding this protein have long been associated with susceptibility to autoimmune disease [32].…”
Section: Designing a Potent Cd40 Agonistmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that engineering CP-870,893 with an IgG1 Fc domain, to enhance binding to FcγRIIB, can improve the potency of CP-870,893 as measured by its ability to invoke antigen-specific T cell immunity in a novel humanized mouse model [31]. FcγRIIB is the only inhibitory Fc receptor and variations in the gene encoding this protein have long been associated with susceptibility to autoimmune disease [32].…”
Section: Designing a Potent Cd40 Agonistmentioning
confidence: 99%
“…While FcγRIIB polymorphisms are known [32], whether these variations will have therapeutic implications for the translation of IgG1-modified CD40 agonists is presently unclear. In addition, the enhanced potency of IgG1 CD40 agonists seen in murine models is associated with an increased capacity to produce transient thrombocytopenia[31]. Reducing the dose of the Fc-modified CD40 agonist, though, was found to diminish the level of thrombocytopenia while still maintaining improved agonist activity compared to the IgG2 isotype [31].…”
Section: Designing a Potent Cd40 Agonistmentioning
confidence: 99%
“…This discrepancy might rely on the expression pattern of hFcgRIIB versus activating hFcgRs in vivo compared to cell lines, in conjunction with the superior capping abilities of the FcgRIIB1 isoform (Figure 1). Interestingly, the use by Dahan and colleagues (Dahan et al, 2016) of similar mutants of two other anti-CD40 mAbs binding different hCD40 epitopes (CD40.1 and CD40.2 clones) indicated that the FcgR-independent agonistic activity of anti-CD40 mAbs is not related to the ability of the mAbs to compete with CD40 ligand (CD40L) binding, as previously suggested (Richman and Vonderheide, 2014).…”
mentioning
confidence: 54%
“…In this issue of Cancer Cell, Dahan and colleagues (Dahan et al, 2016) describe an elegant pre-clinical model to study the mechanism underlying the agonistic effect of anti-human CD40 mAbs. They used transgenic mice that expressed both human CD40 and human FcgRs: hFcgRI, hFcgRIIAH 131 variant (the only hFcgR to markedly bind IgG2; Bruhns et al, 2009), hFcgRIIB, hFcgRIIIA (F 158 variant), and hFcgRIIIB.…”
mentioning
confidence: 97%
“…Dahan described the development of a mouse model fully humanized for its FcγRs and CD40. Using this model, they were able to appropriately assess the activity of human CD40 agonistic Abs by considering both its Fab- and Fc-mediated mechanisms 43 . They discovered that the antitumor activity of the human IgG, including the IgG2 subclass, depends on FcγRIIB-engagement.…”
Section: Introductionmentioning
confidence: 99%